Etyczne problemy w pracy na podstawie opinii pracowników wybranych banków - Rogowski, Robert (Annales. Etyka w Życiu Gospodarczym, 2016)
The paper presents ethical problems of employees in selected banks in Poland. The theoretical part of the paper deals with codes of ethics in banking, especially those concerning the moral aspects of working in banking. The empirical part of the paper presents the results of research on the ethos of bank workers. Quantitative and qualitative analyses were carried out using a specialist Internet forum devoted to the banking sector. The study includes an analysis of hundreds of comments posted on an Internet forum.